Does macroeconomic misery index matter in the micro firm-level earnings Management – performance nexus? Evidence from dynamic Panel threshold regression - Emmanuel Mensah; Joseph Kwadwo Tuffour; Mamdouh Abdulaziz Saleh Al-Faryan (Cogent Economics & Finance, 2023)
Earnings management (EM) and its association with firm performance has been a subject of research interest for decades. This study re-examines the EM-firm performance nexus in a novel way using a nonlinear framework and introducing macro-economic misery index (MI) as a possible threshold variable in the analysis. 52 sampled non-financial listed firms are drawn from nine emerging sub-Saharan African countries spanning a period of 2007-2019. The study employs the dynamic panel threshold estimation approach in analyzing its models. By using MI as a threshold variable, the results show new findings of the performance effect of EM contingent on a uniquely identified MI threshold of 22.51. The study finds that the performance-enhancing effect of EM is realized only when a firm's MI is below the identified threshold. Above this threshold, the effect of EM on performance is negligible or sometimes adverse. The estimated nonlinear effect of EM on firm performance and the threshold of MI can be benchmarks for Africa and other emerging countries. The findings suggest important implications for national governments in adopting policies that help to minimise the economic misery of the citizenry, as they would generally inure to the greater good of businesses and their varying stakeholders.
Keywords: A12; C24; C33; C38; G30; G34; M41; 330; earnings management and firm performance; macroeconomic misery index; national governance quality; Sub-Saharan Africa